Estudio de factibilidad para la creación de una empresa rectificadora de motores en la ciudad de Quevedo, año 2014 - Lomas Morales, yessica Karina (2015)
The current research project lined up to perform a feasibility study to determine the economic and financial technical feasibility for the creation of the company grinding motors in the city of Quevedo in the province of Los Rios. Rectification is a process that helps eliminate desgate linear or circular metal part. At present the different types and uses have made vehicles indispensable for the development of the Daily individuals are necessary, have vehicles to facilitate the mobilization to the different places where people can meet their common needs. The initial investment is $ 150.000.00 which 7% is equity $ 10.500.00 while 93% will be funded by the National Development Bank or $ 139.500.00 five-year term and an interest rate of 11% annual internal rate of return of 63% and the net present value of the investment is $ 84.583.28 with a benefit cost ratio of $ 2.12 recovery time of the investment is 4 years , 8 months and 20 days which indicates that the project is profitable.